2015
DOI: 10.1186/s12866-015-0595-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of reverse-transcription loop-mediated isothermal amplification assay for rapid detection and differentiation of dengue virus serotypes 1–4

Abstract: BackgroundDengue virus (DENV), the most widely prevalent arbovirus, continues to be a threat to human health in the tropics and subtropics. Early and rapid detection of DENV infection during the acute phase of illness is crucial for proper clinical patient management and preventing the spread of infection. The aim of the current study was to develop a specific, sensitive, and robust reverse transcriptase loop-mediated isothermal amplification (RT-LAMP) assay for detection and differentiation of DENV1-4 serotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 42 publications
4
32
0
6
Order By: Relevance
“…The sequences of primers used for RT-LAMP on DENV-4 detection, which has been described by Hu et al, 52 are shown in Table 1.…”
Section: Rt-lamp Amplification Of Dengue Virus In Pet Microchipmentioning
confidence: 99%
“…The sequences of primers used for RT-LAMP on DENV-4 detection, which has been described by Hu et al, 52 are shown in Table 1.…”
Section: Rt-lamp Amplification Of Dengue Virus In Pet Microchipmentioning
confidence: 99%
“…The genome amplification step is monitored by the visible colour change of HNB (hydroxylnaphthol blue) from violet to sky blue as the LAMP reaction proceeds [10,11]. This method can detect approximately 10-copy templates of dengue virus [12]. However, subtyping of each sample requires the use of either a set of four tubes, each of which has the primer mixture for a particular serotype [9], or of one tube that has a single reaction mixture incorporating all primer sets [11].…”
Section: Detection Of Dengue Virus By Loop-mediated Isothermal Amplifmentioning
confidence: 99%
“…We amplified parts of the 3′UTR of the virus, as opposed to a previously published method 22 . We then identified their sequences with the MinION sequencer.…”
Section: Introductionmentioning
confidence: 99%